Evaluating the wind cooling potential on outdoor thermal comfort in selected Iranian climate types. (August 2020) - Roshan, Gholamreza; Moghbel, Masoumeh; Attia, Shady
Abstract: Wind is one of the main factors affecting people's outdoor thermal sensation. Ongoing urbanization and urban densification are transforming the urban climate and complicating the pedestrian-level wind environment. Therefore, the main aim of this research is to evaluate the potential wind-cooling effect on human outdoor thermal conditions. Accordingly, the current research attempts determine the best wind directions for thermal comfort at the studied stations and how these factors will be changed under the effects of global warming. Outdoor thermal conditions were modeled based on the physiologically equivalent temperature (PET) thermal index using RayMan software for the decades of the 2000s and the 2040s in different climate types of Iran (Csb, BWh, Csa, and BSh) To estimate the potential cooling effect of wind, the PET was calculated (1) under actual wind conditions, and (2) under calm wind (0.05 m/s) conditions. Then, the ΔPET for these two conditions, which indicates the cooling potential effect (CPE) of the wind, was calculated for four representative stations (Ardebil, Bandar Abbas, Gorgan, and Shiraz). In comparison with the 2000s, the results indicated that by the 2040s, the predicted wind cooling potential will have increased in Ardebil, Shiraz, Bandar Abbas and Gorgan (CPE of 13.2 °C, 13.1 °C, 11.2 °C, and 11 °C, respectively). Based on the overall average of two climate change scenarios (A2 and B1) used in this study, the occurrence of "comfortable" conditions by the 2040s will have increased in Bandar Abbas, Shiraz, and Ardebil by 1.1%, 0.4%, and 0.3%, respectively, while it will have decreased in Gorgan by 1.5%. Accounting for the cooling effect of wind, the comfort cooling potential of wind is predicted to rise by an average of 1.6 °C in the 2040s compared with the 2000s in all the studied stations. Therefore, this will affect the microclimates positively and could reduce the urban heat island effects. Highlights: The bioclimatic design of outdoor urban spaces can improve the quality of life in the cities. Using new bioclimatic approaches can help reduce the negative impacts of changes of thermal thresholds affected by climate change. Wind cooling potential effect can moderate the strong heat stress condition in urban areas. Wind and its thermal comfort impacts should be taken into account as a moderator especially in urban areas with high potential of heat events occurrence.